Effect of acupuncture therapy on fracture healing in rats with femur fractures - Yilmaz, Seval; Kaya, Emre; Yilmaz, Erhan; Kavakli, Ahmet; Gurbuz, Suleyman; Ozkaraca, Mustafa (Journal Traditional Chinese Med, 2020)
OBJECTIVE: To investigate the effect of acupuncture therapy on fracture healing in rats with femur fractures. METHODS: A total of 10 groups were formed; control group, groups sacrificed on 7th, 14th, and 21st days of fracture formation, groups to which acupuncture was applied for 7, 14, and 21 d, groups to which fracture and acupuncture were applied for 7, 14, and 21 d. A transverse fracture line was formed in femurs of rats by using a Gigli saw. The Kirschner wire was driven retrograde down from the fracture line to proximal part of the bone and then, the fracture was fixed towards distal part. Acupuncture was applied to the rats for 7, 14, and 21 d as 4 sessions per week after formation of the fracture. RESULTS: Malondialdehyde (MDA), reduced glutathione (GSH) levels, catalase (CAT), glutathione-S-transferase (GST), superoxide dismutase (SOD), and glucose-6-phosphate dehydrogenase (G6PD) activities were measured. Despite the increased MDA levels, G6PD and SOD activities reduced during the fracture healing. There was a statistically significant increase in MDA, GSH levels, and G6PD activity in fracture groups compared to control group, but CAT, GST, and SOD activities decreased. The use of acupuncture enhanced callus development and bone mineralization during bone healing. CONCLUSION: The acupuncture therapy can affect suppression of the effects of free oxygen radicals and regulation of the antioxidant enzyme activity in fracture healing. Thus, it is suggested that acupuncture treatment would be beneficial for fracture healing in order to eliminate the negative effects induced by oxygen free radicals. (C) 2020 JTCM. All rights reserved.
Keywords: Femur; Fracture healing; Acupuncture; Malondialdehyde; Antioxidants